2019
DOI: 10.3390/ma12233810
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan Biopolymer from Crab Shell as Recyclable Film to Remove/Recover in Batch Ketoprofen from Water: Understanding the Factors Affecting the Adsorption Process

Abstract: Seafood, a delight for many people, is sold in the market as a wide variety of products. However, seafood industries produce many by-products; for example, during the processing, the heads and shells of shellfish are generated as waste. This results in the generation of a large amount of shell waste that is accumulated over time, inducing a major environmental concern. Effective solutions for recycling shell waste should be taken into consideration, and the extraction of commercially useful substances like chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 35 publications
3
48
0
Order By: Relevance
“…Rizzi, Gubitosa, et al (2019), Rizzi, Lacalamita, et al (2019), Rizzi, Romanazzi, et al (2019)) also reported the study on the adsorption and removal of diclofenac from water by chitosan film. Under the experimental conditions, the maximum adsorption capacity of diclofenac on chitosan film was about 10 mg/g.…”
Section: Physical and Physicochemical Separation Coagulation And Somentioning
confidence: 94%
See 2 more Smart Citations
“…Rizzi, Gubitosa, et al (2019), Rizzi, Lacalamita, et al (2019), Rizzi, Romanazzi, et al (2019)) also reported the study on the adsorption and removal of diclofenac from water by chitosan film. Under the experimental conditions, the maximum adsorption capacity of diclofenac on chitosan film was about 10 mg/g.…”
Section: Physical and Physicochemical Separation Coagulation And Somentioning
confidence: 94%
“…Rizzi, Gubitosa, et al (2019), Rizzi, Lacalamita, et al (2019), Rizzi, Romanazzi, et al (2019) studied and compared the removal efficiency of tetracycline in contaminated water by the olive pomace (OP) and the olive solid wastes/chitosan composite (OSW/CC). Their results showed that the adsorption capacities of OP and OSW/CC were 16 and 1.6 mg/g, respectively.…”
Section: Biological Treatment Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The paper contributed by Rizzi and coworkers introduced the use of chitosan from biowaste (crab shell) to induce the formation of solid films useful for the decontamination of water from emerging pollutants [19]. In particular, ketoprofen was used as a contaminant, and a high percentage of removal, at least 90%, was shown in a short time under the proposed experimental conditions.…”
Section: Waste Materials For Environmental Sciencementioning
confidence: 99%
“…Moreover, five papers were related to the treatment of wastes for environmental applications. Specifically, two papers reported the reuse of egg by-products [18] and crab shell [19] for the removal of biopersistent micropollutants, and two papers reported the reuse of white bamboo fibrils as oil absorbent [20] and a rapid method for the disposal of radioactive contaminated soil waste [21], respectively. The last one reported the use of wheat straw biochar for cobalt sorption from contaminated soil [22].…”
Section: Introductionmentioning
confidence: 99%